Cartilage thickness at the posterior medial femoral condyle is increased in femorotibial knee osteoarthritis: a cross-sectional CT arthrography study (Part 2). Issue 2 (February 2015) - Omoumi, P.; Michoux, N.; Roemer, F.W.; Thienpont, E.; Vande Berg, B.C.
Summary: Objective: To evaluate the thickness of cartilage at the posterior aspect of the medial and lateral condyle in Osteoarthritis (OA) knees compared to non-OA knees using computed tomography arthrography (CTA). Design: 535 consecutive knee CTAs (mean patient age = 48.7 ± 16.0; 286 males), were retrospectively analyzed. Knees were radiographically classified into OA or non-OA knees according to a modified Kellgren/Lawrence (K/L) grading scheme. Cartilage thickness at the posterior aspect of the medial and lateral femoral condyles was measured on sagittal reformations, and compared between matched OA and non-OA knees in the whole sample population and in subgroups defined by gender and age. Results: The cartilage of the posterior aspect of medial condyle was statistically significantly thicker in OA knees (2.43 mm (95% confidence interval (CI) = 2.36, 2.51)) compared to non-OA knees (2.13 mm (95%CI = 2.02, 2.17)) in the entire sample population ( P  < 0.001), as well as for all subgroups of patients over 40 years old (all P  ≤ 0.01), except for females above 60 years old ( P  = 0.07). Increase in cartilage thickness at the posterior aspect of the medial condyle was associated with increasing K/L grade in the entire sample population, as well as for males and females separately (regression coefficient = 0.10–0.12, all P  < 0.001). For the lateral condyle, there was no statistically significant association between cartilage thickness and OA (either presence of OA or K/L grade). Conclusions: Cartilage thickness at the non-weight-bearing posterior aspect of the medial condyle, but not of the lateral condyle, was increased in OA knees compared to non-OA knees. Furthermore, cartilage thickness at the posterior aspect of the medial condyle increased with increasing K/L grade.